Is sleep quality a moderated mediator between perceived stress and depression among stroke patients? - Lina Guo; Miao Wei; Genoosha Namassevayam; Mengyv Zhang; Yvying Xie; Runtang Meng; Yuanli Guo; Yanjin Liu (Frontiers Media S.A., 2024)
BackgroundSleep quality can offer new insights into addressing depression among stroke patients. However, the current understanding of the mechanism by which sleep quality reduces depression is not clear in existing research.ObjectivesThis study aimed to identify the relationships and mechanisms among perceived stress, sleep quality, social support, and depression in stroke patients.MethodsA multicenter cross-sectional study was conducted from January to May 2023. Cluster random sampling was used to recruit 500 stroke patients from five hospitals in Henan Province, China. The Chinese Perceived Stress Scale (CPSS), Pittsburgh Sleep Quality Index (PSQI), Social Support Rating Scale (SSRS), and Hamilton Depression Scale (HAMD-24) were employed to assess perceived stress, sleep quality, social support, and depression, respectively. Data were analyzed using descriptive analysis, Pearson's correlation analysis, and moderated mediation analysis. The study adhered to the STROBE checklist for reporting.ResultsOut of 500 participants, 471 completed the survey (94.2%). After controlling for sex and age, mediation analysis revealed that poor sleep quality partially mediated the relationship between perceived stress and depression (β = 0.184, 95% CI: 0.110, 0.359). Additionally, social support played a moderating role in the mediation model.ConclusionThis study explained the moderated mediation of sleep quality and social support between perceived stress and depression. It provided a theoretical basis for the development of a sleep quality intervention program for reducing depression among stroke patients.